Le révisionnisme allemand en assaut - Derlatka, Tadeusz; Nurowski, Roman; Lesniewski, Andrzej (Poznan Warszawa : Wydawnictwo Zachodnie, 1960)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Koude Oorlog; militarisme; Duitsland